Measurements of excitation spectra and level lifetimes for highly charged neon ions - 王友德 马新文 杨治虎 杜一飞 刘惠萍 赵孟春 郭天瑞 王春芳 (Science China. Mathematics, 1997)
Beam foil experiments were carried out for 47 MeV Ne ions passing through C (39 μg/cm2) and Al (3 4mg/cm2) foils. Highly charged H-, He-, Li-, and Be-like ions were obtained after the foils. The excitation spectra and level lifetimes for these ions were measured, and transition configurations for most measured lines were identified